2016 ASEE Annual Conference &Amp; Exposition Proceedings
DOI: 10.18260/p.26317
|View full text |Cite
|
Sign up to set email alerts
|

A Flipped Classroom Approach to Teaching Transportation Engineering

Abstract: Abstract:The flipped classroom approach has gained increasing popularity in higher education, particularly in STEM fields. In flipped learning, part or all of direct instruction is delivered through online videos and other media, and the class time is used for engaging students in collaborative, hands-on activities. In order to utilize the benefits of this novel teaching approach, a junior-level, introduction to transportation engineering course was converted into a flipped format. This study, conducted in a m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…This work is not dissimilar to other course transitions to a flipped classroom found within the literature [1][2][3][4][5]. However, what is different about this course is its reliance on invited lecturers.…”
Section: Discussionmentioning
confidence: 51%
“…This work is not dissimilar to other course transitions to a flipped classroom found within the literature [1][2][3][4][5]. However, what is different about this course is its reliance on invited lecturers.…”
Section: Discussionmentioning
confidence: 51%
“…Useful short articles include [28] [29]. Also, Karabulut et al, [30] showed that students benefitted from the flipped learning transportation and they recommend their approach to others.…”
Section: Transportationmentioning
confidence: 99%
“…Even if the students are well motivated, it also helps if the class itself is entertaining. Karabulut-Ilgu's suggestion of a "Flipped Classroom" 5 where the passive learning is done outside of class using videos and the in-class time is spent on active learning is a very intriguing idea, but it may not always work for highly theoretical classes. On the one hand, it gives the student the chance to review the videotaped material as many times as needed, until he or she is comfortable with the material; however, it does not give the student the opportunity to ask questions until the activity where this material is assumed to have been already learned.…”
Section: Make the Connection Earlymentioning
confidence: 99%